2008
DOI: 10.1083/jcb.200710052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of inner kinetochore assembly and maintenance in living cells

Abstract: Abbreviations used in this paper: CENP, centromere protein; FCS, fl uorescence correlation spectroscopy; mRFP, monomeric red fl uorescent protein; PCNA, proliferating cell nuclear antigen.The online version of this paper contains supplemental material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
201
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(227 citation statements)
references
References 88 publications
19
201
2
5
Order By: Relevance
“…2). In agreement with these findings, CENP-A nucleosomes are remarkably stable and turn over only upon replication by redistribution to the two sister chromatids (Régnier et al 2005;Jansen et al 2007;Hemmerich et al 2008). Such stability provides further evidence for a key role for CENP-A in the maintenance of centromere identity.…”
Section: Cenp-a: a Key Epigenetic Centromere Marksupporting
confidence: 76%
“…2). In agreement with these findings, CENP-A nucleosomes are remarkably stable and turn over only upon replication by redistribution to the two sister chromatids (Régnier et al 2005;Jansen et al 2007;Hemmerich et al 2008). Such stability provides further evidence for a key role for CENP-A in the maintenance of centromere identity.…”
Section: Cenp-a: a Key Epigenetic Centromere Marksupporting
confidence: 76%
“…Interestingly, a recent study in maize also showed that the in vitro binding of CENP-C to DNA is enhanced and stabilized by the presence of long, single-stranded RNA (12). Fluorescence recovery after photobleaching analysis of CENP-C cell-cycle dynamics revealed that although CENP-C undergoes dynamic exchange throughout most of the cell cycle, CENP-C is stably bound at the mitotic kinetochore (30). The mitotic transcripts generated by the kinetochore-associated RNAPII reported here could function to stabilize the association of CENP-C at the kinetochore during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Importantly, while CENP-A nucleosomes are stably bound to centromeric chromatin, 16 the binding of CCAN proteins appears to be dynamic. [17][18][19] CENP-C and CENP-T serve as a platform for recruitment of the KMN network through pathways that are not yet well understood. [20][21][22][23][24][25][26][27][28][29] From the CCAN components, CENP-N and CENP-C recognize CENP-A.…”
Section: Introductionmentioning
confidence: 99%